Demoralizing labor: Analysis of Priority Objective No. 5 of the National Competitiveness and Productivity Policy (NCPP) - Tello Asencio, Jennifer (2022)
This article aims to present an analysis of the Priority Objective N°5 of the National Competitiveness and Productivity Policy (NCPP) from the perspective of economic anthropology. This objective refers to the creation of conditions to enable the Peruvian labor market to be more dynamic and competitive and to generate decent employment. To do this, we resort to key concepts used in this branch of anthropology, such as the labor theory of value (Marx, 1975; Collins, 2016), that of accumulation by dispossession (Kasmir and Carbonella, 2014), precariousness (Castel, 2014), as well as the theoretical approach of the moral economy (Carrier, 2018; Thompson, 1991; Scott, 1977; Palomera and Vetta, 2016). In the first part, the main aspects of the diagnosis of the Peruvian labor market from the NCPP are presented. Next, the policy measures proposed in the National Competitiveness and Productivity Plan are examined to determine how they fulfill the objective. Afterwards, the NCPP design and approval process is explored. Finally, it is concluded that the approval of this policy should be understood as part of a larger-scale process that aims to stripping workers of their non-wage labor benefits. This dispossession makes workers’ lives precarious and weakens the moral component of the Peruvian economy, that is, respect for the fulfillment of the obligations that people contract with each other in the framework of social relations and economic transactions.